(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the rhyme-forming techniques found in the paremiological units of the Turkish and Azerbaijani languages. The rhymes observed in these proverbs are based on sound repetitions that produce rhythm. These lexical items, often different in meaning, are connected by phonetic similarity in both form and content. Unlike in traditional folk poetry, rhyming words in paremiological expressions display distinctive features. The modification of phonetic elements within individual lexical units contributes to the formation of rhyme. The use of paronyms and alliteration further supports rhyme construction in Turkish and Azerbaijani proverbs. The intrasentential placement of rhyming words, often at the beginning and end of syntagmatic segments, enhances their stylistic value. This type of phonetic harmony—whether involving adjacent or non-adjacent rhyme—adds semantic nuance and expressive richness to paremiological structures.Açar sözlər: paremiya, qafiyə, ritm, fonetik təkrar